Role of HLA-DP polymorphisms on chronicity and disease activity of hepatitis B infection in Southern Chinese. - Danny Ka-Ho Wong (Public Library of Science (PLoS), 2013)
Background and aims The association between HLA-DP single nucleotide polymorphisms (SNPs) and chronic hepatitis B virus (HBV) infection varies between different populations. We aimed to study the association between HLA-DP SNPs and HBV infection and disease activity in the Chinese population of Hong Kong. Methods We genotyped SNPs rs3077 (near HLA-DPA1) and rs9277378 and rs3128917 (both near HLA-DPB1) in 500 HBV carriers (hepatitis B surface antigen [HBsAg]-positive), 245 non-HBV infected controls (HBsAg- and antibody to hepatitis B core protein [anti-HBc]-negative), and 259 subjects with natural HBV clearance (HBsAg-negative, anti-HBc-positive). Inactive HBV carriers state was defined by HBV DNA levels <2,000 IU/ml and persistently normal alanine aminotransferase level for least 12 months. Results Compared to the non-HBV infected subjects, the HBV carriers had a significantly lower frequency of the rs3077 T allele (p = 0.0040), rs9277378 A allele (p = 0.0068) and a trend for lower frequency of rs3128917 T allele (p = 0.054). These alleles were associated with an increased chance of HBV clearance (rs3077: OR = 1.41, p = 0.0083; rs9277378: OR = 1.61, p = 0.00011; rs3128917: OR = 1.54, p = 0.00017). Significant associations between HLA-DP genotypes and HBV clearance were also found under different genetic models. Haplotype TAT was associated with an increased chance of HBV clearance (OR = 1.64, p = 0.0013). No association was found between these SNPs and HBV disease activity. Conclusion HLA-DP SNPs rs3077, rs9277378 and rs3128917 were associated with chronicity of HBV disease in the Chinese. Further studies are required to determine whether these SNPs influence the disease endemicity in different ethnic populations.